2020
DOI: 10.3390/diagnostics10070439
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Osteopontin Levels is Associated with Biochemical Markers of Kidney Injury in Patients with Leptospirosis

Abstract: : Leptospirosis becomes severe, with a fatality rate of >10%, and manifests as severe lung injury accompanied by acute kidney injury. Using urine and blood samples of 112 patients with leptospirosis, osteopontin (OPN), galectin-9 (Gal-9) and other kidney-related biomarkers were measured to understand the pathological and diagnostic roles of OPN and Gal-9 in leptospirosis. Plasma levels of full-length (FL)-OPN (pFL-OPN) (p < 0.0001), pFL-Gal-9(p < 0.0001) and thrombin-cleaved OPN (p < 0.01) were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In our previous study, a receiver operating characteristic (ROC) curve analysis revealed that plasma levels of Gal-9 had the greatest ability to discriminate patients with leptospirosis from healthy control subjects as compared with other markers (AUC: 0.899) ( Table 1 ) [ 63 ]. This finding may indicate that the plasma levels of Gal-9 could reflect the severity of leptospirosis, as they have been reported to do for dengue, malaria, and HIV/OI, given that cytokinemia is also frequently seen in this disease.…”
Section: Galectin-9 In a Variety Of Infectious Diseasesmentioning
confidence: 99%
“…In our previous study, a receiver operating characteristic (ROC) curve analysis revealed that plasma levels of Gal-9 had the greatest ability to discriminate patients with leptospirosis from healthy control subjects as compared with other markers (AUC: 0.899) ( Table 1 ) [ 63 ]. This finding may indicate that the plasma levels of Gal-9 could reflect the severity of leptospirosis, as they have been reported to do for dengue, malaria, and HIV/OI, given that cytokinemia is also frequently seen in this disease.…”
Section: Galectin-9 In a Variety Of Infectious Diseasesmentioning
confidence: 99%
“…These findings indicate the involvement of OPN in kidney injury. A significant increase in urine NAG/Cr (p < 0.05) levels in leptospirosis patients has been described previously, and an increased urine NAG level is a highly specific marker of proximal tubular disease [111]. OPN may be involved in tubular dysfunction and is released by infiltrating inflammatory macrophages in tubules [145].…”
Section: Leptospirosismentioning
confidence: 67%
“…The mechanisms underlying the involvement of OPN cleavage in a cytokine storm are not clear; however, these findings further suggest that the cleaved forms of OPN can be used to monitor the severity of pathological inflammation and the therapeutic effects of tocilizumab in CP patients. [9,111,115]. ****; p < 0.0001, ***; p < 0.001, **; p < 0.01, *; p < 0.05.…”
Section: Coronavirus Disease 2019 (Covid-19)mentioning
confidence: 95%
See 2 more Smart Citations